2006
DOI: 10.1111/j.1349-7006.2006.00313.x
|View full text |Cite
|
Sign up to set email alerts
|

EphA4 receptor, overexpressed in pancreatic ductal adenocarcinoma, promotes cancer cell growth

Abstract: To isolate novel diagnostic markers and drug targets for pancreatic ductal adenocarcinoma (PDAC),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 35 publications
2
52
0
Order By: Relevance
“…However, expression of ephrin ligands was not clearly concordant with that of EphA4 in cancer tissue samples. On the other hand, coexpression of ephrinA3 and EphA4 has been reported to play an important role in pancreatic cancer [19] . These results further support the notion that combinations for the Eph receptors and ephrin ligands depend on tissue-type and/or cancertype [7][8][9][10] .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, expression of ephrin ligands was not clearly concordant with that of EphA4 in cancer tissue samples. On the other hand, coexpression of ephrinA3 and EphA4 has been reported to play an important role in pancreatic cancer [19] . These results further support the notion that combinations for the Eph receptors and ephrin ligands depend on tissue-type and/or cancertype [7][8][9][10] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous microarray and Northern blot analyses have shown that EphA4 expression in normal adult tissues is very restricted [19] . Moreover, overexpression of EphA4 in gastric cancer was observed at the protein level as analyzed by immunohistochemistry and this correlated with depth of invasion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations